"Heavy of Mouth" and "Heavy of Tongue": Weight as a Conceptual Metaphor of Disability. (2nd October 2019) - Stroch, Chani; Nussinson, Ravit; Mentser, Sari; Bar-Anan, Yoav
ABSTRACT: We suggest that disability is metaphorically represented in people's minds as heaviness. In three studies we demonstrate the existence of a mental association between physical weight (light vs. heavy) and disability (non-disabled vs. disabled) as well as its bi-directional causal effects (from weight to disability and from disability to weight). In Study 1 (N = 250), participants exhibited the hypothesized association between the dimensions on both a direct and an indirect measure. Study 2 (N = 191) demonstrated that perceived weight affects the perceived severity of a disability, with the weight of a clipboard held by participants affecting perceptions of a target person's stutter or limp. Study 3 (N = 103) testified to the reverse effect: participants who heard a monologue by someone with a pronounced (as opposed to mild) stutter perceived the clipboard they were holding as heavier and estimated its weight in grams as higher. Our findings may suggest that experiences of weight affect both estimates of the prevalence of disabilities in others and in the self as well as level of identification with the disabled. Theoretical implications are discussed as well.